The Effectiveness of Verb Relay Race in Enhancing Tenth Grade Students’ Mastery of Irregular Verbs at SMA N 1 Wiradesa - A'malana, Arina; Panuntun, Ida Ayu (Education Achievement: Journal of Science and Research, 2025)
Many high school students face difficulties in mastering irregular verbs due to their inconsistent pattern and traditional method which was less engaging for the students. Traditional methods often rely on memorization and repetition, which tend to decrease the students’ motivation and engagement. The aim of this research is to find out whether the Verb Relay Race can improve the students’ mastery of irregular verbs. This research used a quasi-experimental method with pre-test and post-test in both experimental class, who received the Verb Relay Race method, and control class, who was received traditional method. The sample of this research was 61 students of class X.5 and X.7 at SMA N 1 Wiradesa. The research instrument was a fill-in-the-blank test consisting of 15 validated and reliable questions. Descriptive statistics and paired sample t-test were used to analyzed the data using SPSS. The result of the research showed that the experimental class gain score from the average score 48.5 to 74.7, showing a significance improvement in students’ mastery of irregular verbs. Moreover, the students showed a positive attitude through the game in learning irregular verbs, stating that the method was more enjoyable and less stressful. These findings suggested that the Verb Relay Race is fun and effective method for enhancing grammar proficiency, especially irregular verbs in EFL classrooms.